KEMAMPUAN EFEKTIVITAS SEKAM PADI (Oryza sativa) SEBAGAI ADSORBEN TERHADAP PENYERAPAN LOGAM BERAT TIMBAL - Maria Priska Yati; Yusriani Sapta Dewi (FT-USNI, 2022)
The environment is said to be a polluted area, if there is a change in the standards of environmental quality standards which include, water, soil and air. This can happen by several factors, one of which is mining activities. Rice husk is a form of agricultural waste which is a